The Discrepancy Between Standard Histologic WHO Grading of Meningioma and Molecular Profile: A Single Institution Series - Roehrkasse, Amanda M.; Peterson, Jo Elle G.; Fung, Kar-Ming; Pelargos, Panayiotis E.; Dunn, Ian F. (Frontiers in Oncology, 2022)
Introduction: Meningiomas are the most common primary central nervous system (CNS) tumors. They are most often benign but a subset of these can behave aggressively. Current World Health Organization (WHO) guidelines classify meningiomas into three grades based on the histologic findings and presence or absence of brain invasion. These grades are intended to guide treatment, but meningiomas can behave inconsistently with regard to their assigned grade, influencing patient expectations and management. Advanced molecular profiling of meningiomas has led to the proposal of alternative molecular grading schemes that have shown superior predictive power. These include methylation patterns, copy number alterations, and mutually exclusive driver mutations affecting oncogenes, including BAP1, CDKN2A/B, and TERT, which are associated with particularly aggressive tumor biology. Despite the evident clinical value, advanced molecular profiling methods are not widely incorporated in routine clinical practice for meningiomas. Objective: To assess the degree of concordance between the molecular profile of meningiomas and the histopathologic WHO classification, the current method of predicting meningioma behavior. Methods: In a two-year single institutional experience, we used commercially available resources to determine molecular profiles of all resected meningiomas. Copy number aberrations and oncogenic driver mutations were identified and compared with the histopathologic grade. Results: One hundred fifty-one total meningioma cases were included for analysis (85% WHO grade 1, 15% WHO grade 2/3). Chromosomal analysis of 124 of these samples showed that 29% of WHO grade 1 tumor featured copy number profiles consistent with higher grade meningioma, and 25% of WHO grade 2 meningiomas had copy number profiles consistent with less aggressive tumors. Furthermore, 8% harbored mutations in TERT, CDKN2A/B, or BAP1 of which 6% occurred in grade 1 meningiomas. Conclusions: Routine advanced molecular profiling of all resected meningiomas using commercially available resources allowed for identification of a significant number of meningiomas whose molecular profiles were inconsistent with WHO grade. Our work shows the clinical value of integrating routine molecular profiling with histopathologic grading to guide clinical decision making.